Hydrogen flow rate control using an adaptive output feedback second-order sliding mode control for hydrogen production by PEM EL. Issue 12 (2022) - Koundi, M.; Fadil, H. El; Nady, S.; Intidam, A.; Bentalhik, I.; Hizoune, R.
Abstract: This paper deals with the problem of controlling the hydrogen flow rate of the proton exchange membrane electrolyzer (PEM EL through the nominal PEM EL voltage. To achieve this objective an interleaved buck converter (IBC) has been chosen to supply the PEM EL from the DC bus. Therefore, the main objective of this paper is to design an adaptive output feedback control of the IBC- PEM EL system using an adaptive observer-based extended Kalman filter (EKF) and super-twisting sliding mode control (ST-SMC). In the first part, an adaptive observer-based EKF has been developed to estimate the inductors current under measurement noise and unknown PEM EL parameters. In the second part developed an ST-SMC to ensure tight regulation of the electrolyzer voltage to its reference value, equal current sharing between the three parallel legs of the interleaved buck converter, achieve finite-time convergence of electrolyzer voltage, and current, and guarantees the asymptotic stability of closed-loop system. The theoretical analysis and controller performances have been validated using numerical simulation.